Behavior and Academic Performance of Grade 3 Learners of Cuyapo West District - Requito, Rosemarie S; Quimson, Liza L (Southeast Asian Journal of Science and Technology, 2018)
Generally, the study aimed to determine the behavior and academic performance of Grade 3 Learners of Cuyapo West District during the last quarter of the Calendar Year 2018. Descriptive method of research was utilized in the study. Based on the findings of the study, the following conclusions are derived: (1) The Grade 3 pupils of elementary schools in the West District of Cuyapo, Nueva Ecija vary in their profile variables. (2) The pupils often adhere to their behavior in terms of academic learning, classroom condition and group interaction. (3) Pupils performed very satisfactorily in Filipino, Mother Tongue, and ESP. However, satisfactory performances only in Mathematics, English, Science, Araling Panlipunan and MAPEH. On the other hand, they all favored Nutrition Moth celebration. (4) Age, sex, monthly family income, parents’ highest educational attainment deemed significant in the adherence to their behavior. However, birth order and number of siblings did not show any significance. (5) All disciplines are related along pupils’ adherence of their behavior except Filipino subject. and (5) Intervention program is designed to improve the academic performance and behavior of the grade 3 pupils.